The Exfoliation of Graphite Particles in the Vibratory Disk Mill. Issue 9 (28th June 2017) - Aman, Sergej; Aman, Alexander; Hintz, Werner; Trüe, Michael; Veit, Peter; Hirsch, Sören
Abstract: The exfoliation of graphite particles during the treatment in the vibratory disk mill containing commercial sugar was investigated. During the collision of the grinding ring with the grinding chamber wall an intensive stressing of graphite takes place. After treatment in the mill, the resulting dark paste was solved in water and subjected to 10 min sonication. The suspension was centrifuged to remove the not exfoliated multilayered particles. Analysis of Raman spectra shows the presence of graphite sheets in suspension. The represented method of exfoliation is environmentally friendly and scalable. Abstract : The production test of multilayer graphene was carried out in the vibratory disk mill. In terms of a developed model it was shown that the exfoliation occurs in high viscous medium. Analysis of Raman spectra shows the presence of high number of defects in graphene, which can be useful for production of capacitive electrodes and batteries.